Overeducation, Earnings and Job Satisfaction among Graduates in China - Melanie K. Jones; Ezgi Kaya; Jiarui Nan (Institute of Labor Economics (IZA), 2024)
Exploiting rich nationally representative longitudinal data from the China Family Panel Studies this paper explores the relationship between overeducation, earnings and job satisfaction among graduates in China. We find consistent evidence, across multiple measures of overeducation, of wage and job satisfaction penalties that are not explained by personal and work-related characteristics. Despite attention within the literature, we find a modest role for differences in academic subject and, cognitive and non-cognitive skills as drivers of these penalties. In contrast, controlling for time-invariant unobserved heterogeneity reduces the size and, in many cases, removes the statistical significance of overeducation penalties, aligned to the importance of other unobserved individual heterogeneity.
Keywords: J24; J28; J31; 330; overeducation; China; earnings; job satisfaction; cognitive and non-cognitive skills; unobserved heterogeneity